Effect of multiple adhesive coating on the microshear bond strength and surface microhardness of bonded dentin after using four adhesives - Torabzadeh H; Ghasemi A; Asadian F; Akbarzadeh A (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: In this in-vitro study, the effect of multiple adhesive coating on the microshear bond strength of composite to dentin and surface microhardness of dentin after treatment with four adhesives (One Step Plus, One Step, Single Bond, Single Bond 2) were evaluated. "nMaterials and Methods: One hundred intact human molars were cut to obtain disks of dentin having 2 mm thickness. For the microshear bond test, sixty disks were randomly divided into four groups. In each group one type of adhesive was used. In one half of a disk two layers and in another half six layers of adhesive were applied. Cylinders with 1mm height was filled with a composite and light cured. The cross-head speed was 0.5 mm/min. Vickers microhardness was tested on forty dentin disks which divided into four groups and prepared in the same manner used for microshear bond test. Data were analyzed by Two-way ANOVA and Tukey tests. "nResults: The highest and lowest bond strength were recorded as 29.49 ± 5.74 MPa (One Step Plus; 6 layers), and 21.23 ± 4.83 MPa (One Step Plus; 2 layers), respectively. The results indicated that One Step Plus bond strength in 6 Layers was significantly higher than 2 layers. The highest and lowest dentin hardness values were"n39.08 ± 8.34VHN (Single Bond; 2 layers) and 28.53 ± 5.98 VHN (One Step Plus; 6 layers). None of the adhesives exhibited significant difference in hardness with regards to the layers applied (P>0.05). Presence of filler in adhesives had no significant effect on bond strength (P=0.05) whereas caused significant decrease in the dentin microhardness (P<0.05). In addition, type of solvent had significant effect on the bond strength and bond strength was significantly higher in acetone-base adhesives (P<0.05). However, dentin microhardness was significantly higher in the ethanol-base adhesives (P<0.05). "nConclusion: Multiple adhesive coating had no influence on the microshear bond strength of composite to dentin and dentin surface microhardness. It was dependent on the type of adhesive used.